Bentuk Aktivitas Siswa yang Menunjang Keseimbangan Tumbuh Siswa Kelas V SD Berlian - Muhammad Hatim (STKIP AL HIKMAH SURABAYA, 2022)
Motor balance is one of the motor skills that need to be developed by children. Motor balance plays an important role in every activity. Elementary school age children are the age in motor development. Motor development is strongly influenced by the environment and activities that become habits of children. This study aims to determine the form of student activity that can support body balance. The sample in this study was the fifth grade students of SD Berlian with a total of 6 students with a total of 22 students. The average score of students is 84.2. From the results of interviews regarding aspects of light, moderate and heavy physical activity, 5 students tend to do strenuous activities at home.